2006
DOI: 10.1073/pnas.0600875103
|View full text |Cite
|
Sign up to set email alerts
|

V1a vasopressin receptors maintain normal blood pressure by regulating circulating blood volume and baroreflex sensitivity

Abstract: Arginine-vasopressin (AVP) is a hormone that is essential for both osmotic and cardiovascular homeostasis, and exerts important physiological regulation through three distinct receptors, V1a, V1b, and V2. Although AVP is used clinically as a potent vasoconstrictor (V1a receptor-mediated) in patients with circulatory shock, the physiological role of vasopressin V1a receptors in blood pressure (BP) homeostasis is ill-defined. In this study, we investigated the functional roles of the V1a receptor in cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 35 publications
8
149
1
Order By: Relevance
“…Among them, AVP is known to be a potent vasoconstrictor that stimulates the proliferation of VSMC [12,13,18]. While three receptor subtypes exist for AVP (V1a, V1b and V2), V1a receptor has been reported to play the dominant role in cardiovascular system and behavior [41,42]. It has recently been reported that V1a-/-mice showed lower blood pressure through the reduction of blood volume and the impairment of the baroreceptor reflex [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, AVP is known to be a potent vasoconstrictor that stimulates the proliferation of VSMC [12,13,18]. While three receptor subtypes exist for AVP (V1a, V1b and V2), V1a receptor has been reported to play the dominant role in cardiovascular system and behavior [41,42]. It has recently been reported that V1a-/-mice showed lower blood pressure through the reduction of blood volume and the impairment of the baroreceptor reflex [42].…”
Section: Discussionmentioning
confidence: 99%
“…While three receptor subtypes exist for AVP (V1a, V1b and V2), V1a receptor has been reported to play the dominant role in cardiovascular system and behavior [41,42]. It has recently been reported that V1a-/-mice showed lower blood pressure through the reduction of blood volume and the impairment of the baroreceptor reflex [42]. On the other hand, V1b-/-mice have been reported to show mildly impaired social recognition [43], but so far little information is provided on cardiovascular disorder in V1b-/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…The first involves the hypothalamic magnocellular acting through its peripheral cognate V1a receptor [49,50] , a G-protein-coupled receptor signaling via phospholipase C [51][52] , is largely responsible for regulating water homeostasis and blood pressure [49,53] . The second system consists of parvocellular neurons within the PVN; these neurons produce both AVP and CRH peptide hormones [55] .…”
Section: Arginine Vasopressinmentioning
confidence: 99%
“…58 (4) Interestingly, mice with deletion of the V1aR exhibit a lower BP as a result not of a reduced vasoconstriction but of a lower extracellular fluid volume. 59 In summary, these results provide a better knowledge of the respective V2R-and V1aR-dependent effects of AVP on sodium excretion in rats. Whether a similar balance between V1aR-and V2R-dependent effects occurs in humans remains to be determined.…”
Section: Integration Of V2r and V1ar Effectsmentioning
confidence: 99%